PEDAGOGICAL BASIS OF FORMING INHERENT IMMUNITY IN YOUTH. (Universal International Scientific Journal, 2026)
This thesis analyzes the pedagogical foundations of the formation of ideological immunity in young people. The purpose of the study is to identify the factors that develop critical thinking, information literacy and a stable position based on values ​​in the educational environment. The methodology is a combination of conceptual analysis, pedagogical observation and diagnostic approaches. As a scientific innovation, the modeling of ideological immunity in the form of a system of competencies and the conditions for its formation are based.
Keywords: Ideological immunity; education; information literacy